Aspectos fisiológicos de plantas de abacaxi (Ananas comosus L. Merril) sob cultivo hidropônico e convencional associado ao estudo molecular do florescimento - Gurgel, Géssica Bezerra (2017)
The production of pineapple (Ananas comosus var. comosus) presents many obstacles, such as delayed culture cycle, low seedling production via propagative phase, non-uniformity in its natural flowering and the emergence of diseases, such as fusariosis. Thus, the in vitro propagation technique gains importance for large-scale production of plant sources with better phytosanitary quality. However, these plants must undergo an adaptation process (acclimatization) in order to survive when taken to the field. The objective of the first paper was to determine if non-acclimatized plants can survive under hydroponic and field conditions, and to compare these to acclimatized plants in hydroponic and field cultivation. We verified that non-acclimatized plants can develop under hydroponic conditions, but not under field conditions; and that the development of the aerial part of plants under hydroponic conditions does not differ from that of plants in the field, but present superior root support. The use of better seedlings can generate plants with potential for quicker development and flowering, despite little understanding of the flowering process of pineapples as well as in other species. Therefore, the second work aimed at investigating the percentage of flowering, performance of genes related to the induction to flowering, such as genes from the ethylene production route, AcACS2 and AcACO1, as well as the flowering integrating gene AcFT, under the influence of 1-MCP (inhibitor for ethylene performance) and Ethrel® (flowering stimulator), as well as its combined effect over 12 hours of the application of the other. In this experiment, the use of 1-MCP, when applied alone, stimulated flowering and, when used after the Ethrel®, flowering was delayed. However, this does not decrease the percentage of flowering. The AcACO1 gene was little expressed in the pineapple leaf up to 24 hours after treatments when compared to the control.